2023
DOI: 10.7150/jca.81915
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Validation of Protein Expression-related Prognostic Models in Clear Cell Renal Cell Carcinoma

Abstract: Objective: To construct a prognostic evaluation model for clear cell renal cell carcinoma (ccRCC) patients using bioinformatics method and to screen potential drugs for ccRCC . Methods: ccRCC RNA sequencing data, clinical data, and protein expression data were downloaded from the TCGA database. Univariate Cox and Lasso regression analyses were performed on the combined data to screen out the proteins related to the prognosis, and they were included in a multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“… 39 More studies have found that precision medicine is the key to improving ccRCC outcomes; however, because of the lack of reliable biomarkers, precision medicine is severely limited in the treatment of ccRCC. 40 , 41 , 42 Exosomes have the advantages of easy availability, non‐invasive examination, and tumor specificity. 24 Meanwhile, due to their high mobility and lipid bilayer structure, they can easily passthrough biological membranes and protect rich bioactive substances present inside the membranes from degradation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 39 More studies have found that precision medicine is the key to improving ccRCC outcomes; however, because of the lack of reliable biomarkers, precision medicine is severely limited in the treatment of ccRCC. 40 , 41 , 42 Exosomes have the advantages of easy availability, non‐invasive examination, and tumor specificity. 24 Meanwhile, due to their high mobility and lipid bilayer structure, they can easily passthrough biological membranes and protect rich bioactive substances present inside the membranes from degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is the preferred treatment for ccRCC; however, due to the high aggressiveness and drug resistance of ccRCC, 20%–40% of patients with ccRCC experience recurrence and metastasis after surgery 39 . More studies have found that precision medicine is the key to improving ccRCC outcomes; however, because of the lack of reliable biomarkers, precision medicine is severely limited in the treatment of ccRCC 40–42 . Exosomes have the advantages of easy availability, non‐invasive examination, and tumor specificity 24 .…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to the low expression group, there was a signi cant increase in mast cell activation (P < 0.001) and macrophage M0 (P < 0.05) in the high expression group. It is evident that various immune in ltrates can impact a patient's telomeres, which in turn can alter prognostic markers and immunotherapy targets for cervical cancer 21,22 . (Figure 6A) Next, we mapped the correlated heat maps of differential genes and immune cells to determine the effects of differential genes on immune function in CC patients.…”
Section: Correlation Analysis Between Risk Score and Immune Responsementioning
confidence: 99%